Pop-up Digital for Disability Tunagrahita Pencegahan Pelecahan Seksual pada Anak Tuna Grahita Di SLB Samudra Lavender - Januarti, Luluk; Suryaningsih, Merlyna; Aini, Qurrotu (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2023)
Background: Children with disabilities, especially mentally retarded, have difficulty distinguishing between appropriate and inappropriate touches, which will make it difficult for disabled children to identify actions that lead to sexual harassment directed at them. Intellectual disability or mental disability is a condition where a person's intelligence development experiences obstacles so that they do not reach the optimal stage of development. Digital pop up books are very easy to understand in the learning process and are an effective medium in providing sexual education for mentally retarded children. Purpose: The aim of this community service is to increase awareness of mentally retarded teenagers about preventing sexual violence through digital pop up book media. Method: The stages include planning and preparation, implementation of service activities with workshops, Popi Dita fungame, barcode story corner hut and evaluation. The activity was held on Wednesday 7 June 2023 at SLB Samudra Lavender Bangkalan. Measuring the success of this digital pop up book media uses a pre-test and post-test with a questionnaire containing 16 short questions. Result: The results showed an increase in student knowledge scores from 4.95 to 7.36. The paired t-test obtained a p- value of 0.019 which shows that sexual violence prevention interventions can increase the knowledge or awareness of mentally retarded children regarding the prevention of sexual violence. Conclusion: This activity was successfully carried out with high participation and enthusiasm from students in taking part in this activity. It is hoped that this pop up book can be a useful educational tool for schools in an effort to minimize the number of victims of sexual violence.